Seminal plasma lipid profiles of differential cryotolerance of semen in Mediterranean Buffalo bulls. Issue 4 (25th December 2022) - Luo, Xi; Ren, Xuan; Huang, Shihai; Li, Yanfang; Xue, Qingsong; Shi, Deshun; Li, Xiangping
Abstract: The cryotolerance of semen obtained from Mediterranean buffalo bulls usually is more likely to deteriorate during the summer. To obtain the optimal sperm for fertility, the physiological status and reproductive performance of Mediterranean buffalo bulls in the summer and spring were first analysed by assessing blood serum and seminal plasma samples; then, the lipid profiles of seminal plasma were investigated by LC–MS/MS. The T, T3 and SOD levels of serum and seminal plasma in the spring were significantly higher than in the summer ( p < .05). The results suggest that T3 level is positively correlated with semen cryotolerance; sphingolipids are potential markers for semen cryotolerance of Mediterranean buffalo. To our knowledge, this is the first report of targeted lipidomics in semen cryotolerance.